Análisis de la gastronomía y su influencia en el turismo en el cantón Vinces, año 2021 - Ledesma Soto, Washington Geovanny (2022)
The research was carried out with the purpose of analyzing and publicizing the importance of the gastronomy that is offered in the Vinces canton, this will allow the concurrence of tourists who will be able to taste the variety of typical dishes that are elaborated from generation to generation and with this would improve the economy of this sector of the Province of Los Ríos. The idea of the project was born due to the general ignorance and the lack of diffusion of the tourist places that offer the local gastronomy of the Vinces Canton. In recent years in Ecuador, several tourism sectors have been promoted in each of its regions, each one has incredible landscapes and a diverse climate, thus existing, a variety of exquisite cuisine, where all the provinces have their own cultures and traditions. Therefore, the research has a general objective that had as its purpose the analysis of the gastronomy and the tourist places of the Vinces canton. Through the use of the qualitative approach, the field research, also using the interview as a technique, with it we proceeded to collect the information that allowed us to obtain the data that help to understand the theme of this work in the aforementioned canton. In addition, it is necessary to mention that the sources used as reference allow for a broader knowledge of gastronomy and tourism development. Finally, with the information obtained, some solutions to the problems found in relation to the proposed topic can be determined.